Child maltreatment (v.3) - Eileen Munro (ed.); Trish Hiddleston (ed.) (London: Sage Publications Ltd., 2015)
"The protection of children from maltreatment is a worldwide challenge. Social context plays a significant role in both the definition and society's responses to child maltreatment. The core concept of child maltreatment is socially constructed with variations in its meaning over time and between cultures, creating significant challenges and resulting in a tension between respecting different cultures yet having one law or standard applicable for all children. This Major Work serves a significant function in pulling together literature demonstrating the different lessons that have been learned, pulling out common elements where possible, and helping to clarify the nature of the differences."--Publisher's website.
Formerly CIP.
Keywords: Malnutrition Child; Child Abuse; Peadiatric Health; Child Welfare; Social Sciences